Structure analysis, tuning photoluminescence and enhancing thermal stability on Mn4+-doped La2-xYxMgTiO6 red phosphor for agricultural lighting. Issue 12 (15th August 2020) - Gai, Shujie; Zhu, Haifeng; Gao, Peixin; Zhou, Cheng; Kong, Zihui; Molokeev, Maxim S.; Qi, Zhiyong; Zhou, Zhi; Xia, Mao
Abstract: Currently, phosphor-converted LEDs (pc-LEDs) are revolutionizing the industry of plant growth lighting. To meet the requirements of this technology, phosphors with tunable photoluminescence, high thermal stability and luminous intensity are required. Herein, we found that the simple substitution of yttrium for lanthanum in La2 MgTiO6 :Mn 4+ (LMT:Mn 4+ ) system could satisfy above three criteria simultaneously. The photoluminescence properties can be regulated by continuously controlling the chemical composition of La2-x Yx MgTiO6 :Mn 4+ solid solution. The La sites are occupied by Y ions, causing a significant blue shift in the emission spectra which owing to the change of local crystal field strengthen. Meanwhile, the thermal stability and decay lifetimes are also varied due to the variation of local structure and band gap energy. The thermal stability of the material reaches 83.5% at 150 °C, which is better than the reported La2 MgTiO6 :Mn 4+ and Y2 MgTiO6 :Mn 4+ phosphors. The electronic luminescence (EL) of pc-LED devices using La2-x Yx MgTiO6 :Mn 4+ red phosphor is evaluated, which matching the absorption regions of plant pigments well, reflecting the superiority of the studied phosphors in plant growth lighting areas.